Reductive Ring-Opening 1,3-Difunctionalizations of Arylcyclopropanes with Sodium Metal - Wang, Shuo; Kaga, Atsushi; Yorimitsu, Hideki (Synlett, 2020)
Sodium dispersion promotes reductive ring opening of arylcyclopropanes. The presence of a reduction-resistant electrophile, such as methoxypinacolatoborane, epoxide, oxetane, paraformaldehyde, or chlorotrimethylsilane, during the reductive ring opening event leads to the formation of 1,3-difunctionalized 1-arylalkanes by immediate trappings of the resulting two reactive carbanions. In particular, the ring-opening 1,3-diborylations of arylcyclopropanes afford 1,3-diborylalkanes with high syn selectivity.
Keywords: carbanions; cleavage; diastereoselectivity; electron transfer; metalation; reduction; ring opening; sodium